2017
DOI: 10.1016/j.jgeb.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bioactive metabolites producing marine Streptomyces parvulus strain sankarensis-A10

Abstract: The significance and frequency of marine microorganisms as producers of bioactive metabolites-a natural source of drug discovery had varied significantly during the last decades, making marine ecosystem a huge treasure trove of novel isolates and novel compounds. Among the twelve actinomycetes isolated from marine sediment sample (Lat. 17°41′962″N, Long. 83°19′633″E), amylase, protease, lipase and cellulase activities were exhibited by 8,7,4,3 isolates respectively. Five isolates exhibited l-asparaginase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
2
23
0
1
Order By: Relevance
“…Most of these compounds were isolated from terrestrial sources (Barka et al, 2016;Van Der Meij et al, 2017). However, there were reports recently, where their marine counterparts were also recognized as a source of bioactive compounds (Shaik et al, 2017;Yang and Song, 2017;El-Gendy et al, 2018;Kemung et al, 2018;Subramani and Sipkema, 2019). The condition in the marine environment is remarkably different from that of the terrestrial environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these compounds were isolated from terrestrial sources (Barka et al, 2016;Van Der Meij et al, 2017). However, there were reports recently, where their marine counterparts were also recognized as a source of bioactive compounds (Shaik et al, 2017;Yang and Song, 2017;El-Gendy et al, 2018;Kemung et al, 2018;Subramani and Sipkema, 2019). The condition in the marine environment is remarkably different from that of the terrestrial environment.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the genus Streptomyces of the phylum Actinobacteria are soil saprophytes that are known producers of antibiotics (Shaik et al, 2017;Yang and Song, 2017;Kemung et al, 2018;Yang et al, 2020). These microorganisms contain high GC content in their DNA sequences and are reported to have antibiotic-producing biosynthetic gene clusters (BGC) (Hopwood, 2007;Dhakal et al, 2017;Romano et al, 2018) that produces about 75% of the clinically available antibacterial drugs in the market (Kemung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all three isolates from oil palm plantation in this study were able to use cellulose as carbon source. Cellulolytic ability was not reported in S. parvulus except from a marine origin (Shaik et al, 2017), which could dispose cellulosic wastes added to its environment. The palm wastes in the oil palm plantation could have triggered in the isolates, the ability to utilise cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…was the compound 2,4-bis (1,1-dimethylethyl) phenol. In the same way,Shaik et al (2017) found three Streptomyces isolates with an antifungal activity which produced the bioactive metabolites alpha-amylase, lipase, protease and cellulase Atta (2015). mentioned that S. torulosus produces tunicamycin, a broad-spectrum antibiotic against Gram-positive and Gram-negative bacteria, and unicellular and filamentous fungi.…”
mentioning
confidence: 88%